EMERGENCY TROLLEYS: AVAILABLE AND MAINTAINED BUT ARE THEIR LOCATIONS KNOWN? - Sawsan Ghonaimy; Yahya Khedr; Ahmed Boraei (European Scientific Journal, ESJ, 2013)
Emergency trolleys are developed and placed in strategic locations to improve the efficiency of the medical teams’ response to emergencies. We conducted a survey to assess the team’s knowledge of the presence and location of these trolleys in the Ambulatory Care Hospital in Glasgow, Scotland. The results highlighted a considerable deficiency in the knowledge of these trolleys’ locations in the unit. We anticipate this problem to be much more common than expected. We suggest that similar surveys should be conducted as part of the regular audits in all units and should involve all staff involved in such emergencies.